Changes in the gut microbiota composition and the plasma ghrelin level in patients with Helicobacter pylori-infected patients with eradication therapy. Issue 1 (26th November 2017) - Yanagi, Hidetaka; Tsuda, Ayumi; Matsushima, Masashi; Takahashi, Shunsuke; Ozawa, Genki; Koga, Yasuhiro; Takagi, Atsushi
Abstract : Objective: To investigate the influence of antimicrobials on both the gut microbiota structure and the plasma ghrelin level using Helicobacter pylori -infected patients who underwent eradication therapy. Design: Twenty H. pylori -infected patients (mean age 68.3 years old) who underwent eradication therapy participated in the study. For the therapy, patients had 1 week of triple therapy consisting of amoxicillin, clarithromycin and proton-pump inhibitors. Stool and blood samples were obtained before (S1), immediately after (S2) and/or 3 months after (S3) the therapies. The concentrations of ghrelin and leptin in the blood were assayed using an ELISA. The V3-V4 region of the 16S rRNA gene was amplified using bacterial DNA from the stool, and about 50 000 high-quality amplicons per sample were grouped into operational taxonomic units for bacteriological analyses. Results: The Bacteroidetes:Firmicutes (B:F) ratio was significantly greater at S3 than S1 (P<0.01). This increase in the B:F ratio between S3 and S1 was found in 15 out of 20 patients. A significant decrease in the concentration of active ghrelin (P=0.003) in the plasma was observed between S3 and S1. There was a statistically significant correlation between the rate of patients whose B:F ratio increased and that of patients whose active ghrelin level decreased between S3 and S1 according to Fisher's exact probability test (P=0.03). Conclusions: Changes in the gut microbiota, such as the B:F ratio after treatment with antimicrobials, might cause a change in the plasma ghrelin level, as the direct and earliest target of antimicrobials would be the microbiota rather than the hormone-secreting system.